Analysis of Online Travel Agent Reservation to Increase Room Occupancy at Nandini Jungle Resort & Spa - Ni Putu Ethika Febriyanthi; I Gusti Agung Bagus Mataram; Ni Nyoman Sri Astuti; I Nyoman Winia; Solihin (International Journal of Glocal Tourism, 2022)
Purpose: The purpose of this study was to determine the application of promotions for online travel agents at Nandini Jungle Resort & Spa and to find out how much influence online travel agents have to increase room occupancy rates at Nandini Jungle Resort & Spa. Research methods: The research data was obtained through the process of interview, observation, and documentation. Techniques Data analysis is done by using qualitative analysis and quantitative descriptive analysis. Findings: Qualitative analysis was carried out on primary data through interviews and direct observation to find out the promotions carried out in hotels for online travel agents to increase room occupancy rates at Nandini Jungle Resort & Spa. Quantitative descriptive analysis was performed on secondary data, such as classical assumption test and simple linear regression analysis, with the help of the IBM SPSS version 26 program. Implication: If the reservation variable through online travel agents increases by 1 unit, the resulting room occupancy rate will increase by 0.318 units. The regression coefficient b = 0.318 indicates the amount of additional room occupancy for each additional reservation through an online travel agent.